A Phenomenological Study on the Difficulties of Ukrainian Immigrants in Learning Languages - Yalçın, Gülşah; Yavuz, Serdar (Asya Publishing and Consultancy, 2025)
Individuals or groups are forcibly displaced due to economic problems, wars, terrorism, political conflicts, and discrimination based on gender, ethnicity, or religion. War-induced migration often leads to movement towards neighboring countries, creating challenges for host nations like housing, healthcare, basic needs, and education. Similarly, the Russia-Ukraine War, starting in 2022, led many Ukrainians to migrate to Türkiye and required them to learn Turkish, along with their efforts to work and continue their education in Türkiye. This study aims to identify Ukrainian students’ challenges when learning Turkish and Turkish instructors’ experiences and problems when teaching Turkish to these students, which offers solutions to the language learning/teaching process. Hence, to deeply understand Ukrainian students’ and Turkish instructors’ experiences, we adopted a phenomenological study and gathered the data through focus group discussions with students (n=8) and instructors (n=5). Utilizing the content analysis, the study revealed that Ukrainian students learn Turkish to settle in Turkey, continue their education, and find employment. Notably, both students and instructors indicated difficulties in productive skills due to the lack of practice. Students also find learning Turkish challenging because it belongs to a family of different languages with different alphabets. The study suggested activities to develop students’ language skills. © 2025, Asya Publishing and Consultancy. All rights reserved.
Keywords: foreign students; language learning difficulties; phenomenological study; teaching Turkish to foreigners; Ukrainian migrants